Soil physical quality and sugarcane yield with the use of inter-row chiseling - Sá, Marcos Aurelio Carolino de; Santos Junior, João de Deus Gomes dos; Franz, Claudio Alberto Bento; Rein, Thomaz Adolpho (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of inter-row chiseling on root growth, soil compaction, and sugarcane ratoon yield in the Brazilian Cerrado. The study was conducted for five years, from 2009 to 2013, in a very clayey Rhodic Acrustox, in the municipality of Bom Jesus, in the state of Goiás, Brazil. A randomized complete block design was used comprising two treatments, with and without post-harvest interrow chiseling, and four replicates. Stalk and sugar yields, soil bulk density, degree of compaction, least limiting water range, and specific mass of roots were evaluated. Soil chiseling did not affect stalk or sugar yields, root density, nor soil physical attributes. Critical bulk density for root growth was 1.33 g cm-3, which corresponds to a degree of compaction of 87.9%. Critical soil resistance to root penetration is 3.8 MPa.